Oh crap! potty training : everything modern parents need to know to do it once and do it right - Glowacki, Jamie (Gallery Books, 2024)
"Worried about potty training? Let Jamie Glowacki, potty-training expert, show you how it's done. Her six-step, proven process to get your toddler out of diapers and onto the toilet has already worked for tens of thousands of kids and their parents."--Amazon.